DIRECTION FINDING OF HF SIGNALS SCATTERED BY IONOSPHERIC IRREGULARITIES USING SMALL SIZE ANTENNA - Galushko, V. G.; Zalizovski, A. V.; Kascheev, S. B.; Pikulik, I. I.; Charkina, O. V. (Видавничий дім «Академперіодика», 2016)
PACS number: 94.20.Bb Purpose: A modification of the Doppler Interferometry Technique is suggested to enable estimating angles of arrival of comparatively broadband HF signals scattered by random irregularities of the ionospheric plasma with the use of small-size near-omnidirectional antennas.Desing/methodology/approach: The technique is based on the measurements of cross-spectra phases of the probe radiation recorded at least in three spaced points.Findings: The developed algorithm has been used to investigate the angular and time-and-frequency characteristics of HF signals propagating at frequencies above the maximum usable one for the direct radio path Moscow–Kharkiv. The received signal spectra show presence of three families of spatial components attributed, respectively, to scattering by plasma irregularities near the middle point of the radio path, ground backscatter signals and scattering of the sounding signals by the intense plasma turbulence associated with auroral activations. It has been shown that the regions responsible for the formation of the third family components are located on the equatorial slope of the maximum of the precipitating particle energy. The drift velocity and direction of the polar ionosphere plasma has been determined.Conclusions: The obtained estimates are consistent with the classical conception on the magnetospheric convection and plasma convection in the polar regions and do not contradict to the results of investigations of the auroral ionosphere dynamics using the SuperDARN network.Key words: ionospheric plasma, scattering, direction finding, polar ionosphere, auroral oval, velocity and direction of plasma driftManuscript submitted 01.06.2016Radio phys. radio astron. 2016, 21(3): 231-241 REFERENCES1. Afraimovich, E. L., 1982. Interference methods of ionospheric radio sounding. Moscow: Nauka Publ. (in Russian). 2. Reinisch, B. W., 1996. Modern Ionosondes. In: H. Kohl, K. Schlegel, eds. Modern Ionosphere Science. Katleburg-Lindau: European Geophysical Society, pp. 440–458. 3. Reinisch, B. W. and Galkin, I. A., 2008. A new digisonde for research and monitoring applications. In: XXIX GA URSI, August 7-16, 2008: Abstracts. Chicago, Illinois, USA, p. 131. 4. REINISCH, B. W., SCALI, J. L. and HAINES, D. M., 1998. Ionospheric drift measurements with ionosondes. Ann. Geophys. vol. 41, no. 5-6, pp. 695–702. DOI: 10.4401/ag-3812. 5. GALUSHKO, V. G., 1997. Frequency-and-angular sounding of the ionosphere. Telecommunications and radio engineering. vol. 51, no. 6-7, pp. 1–6. DOI: https://doi.org/10.1615/TelecomRadEng.v51.i6-7.10 6. Galushko, V. G., Yampolski, Y. M. and Reinisch, B. W., 2000. Frequency-and-Angular Sounding of the Ionosphere with the Use of a DPS Receive System. In: Progress in Electromagnetics Research Symposium (PIERS-2000), July 5-14, 2000: Proceedings. Cambridge, MA, USA, p. 603. 7. Galushko, V. G. and Lytvynenko, G. V., 2001. Recovering the Three-Dimensional Structure of Ionospheric Electron Density Distribution by Angular-and-Frequency Sounding. Radio Phys. Radio Astron. vol 6, no. 3, pp. 222–229 (in Russian). 8. GALUSHKO, V. G., BELEY, V. S., KOLOSKOV, A. V., YAMPOLSKI, Y. M., PAZNUKHOV, V. V., REINISCH, B. W., FOSTER, J. C and ERICKSON, P., 2003. Frequency-and-angular HF sounding and ISR diagnostics of TIDs. Radio Sci. vol. 38, is. 6, id. 1102. DOI: https://doi.org/10.1029/2002RS002861 9. PAZNUKHOV, V. V., GALUSHKO, V. G. and REINISCH, B. W., 2012. Digisonde observations of TIDs with frequency and angular sounding technique. Adv. Space Res. vol. 49, no. 4, pp. 700–710. DOI: https://doi.org/10.1016/j.asr.2011.11.012 10. GALUSHKO, V. G., KASCHEEV, A. S., PAZNUKHOV,V. V., YAMPOLSKI, Yu. M. and REINISCH, B. W., 2008. Frequency-and-angular sounding of traveling ionospheric disturbances in the model of three-dimensional density waves. Radio Sci. vol. 43, is. 4, id. RS4013. DOI: https://doi.org/10.1029/2007RS003735 11. BRAUDE, S. Ya., MEN', A. V. and SODIN, L. G., 1978.The UTR-2 decameter wavelength radio telescope. In: Antenny. Moscow: Svyaz'. is. 26, pp. 3–15 (in Russian). 12. Gething, P. J., 1978. Radio direction-finding and the resolution of multicomponent wave-fields. Stevenage, England: Peter Peregrinus. 13. BIBL, K. and REINISCH, B. W., 1978. The Universal digital ionosonde. Radio Sci. vol. 13, is. 3, pp. 519–530. DOI: https://doi.org/10.1029/RS013i003p00519 14. RYTOV, S. M., KRAVTSOV, Yu. A. and TATARSKI, V. I., 1978. Introduction to statistical radiophysics. Part 2: Random fields. Moscow: Nauka Publ. (in Russian). 15. Kashcheyev, S. B., Zalizovski, A. V., Sopin, A. A. and Pikulik, I. I., 2013. On the possibility of bistatic HF ionospheric sounding by exact time signals. Radio Phys. Radio Astron. vol. 18, no. 1, pp. 34–42 (in Russian). 16. Brunelli, B. E. and Namgaladze, A. A., 1988. Physics of the ionosphere. Moscow: Nauka Publ. (in Russian). 17. JAYACHANDRAN, P. T., Macdougall, J. W., ST-MAURICE,J.-P., MOORCROFT, D. R., NEWELL, P. T. and PRIKRYL, P., 2002. Coincidence of the ion precipitation boundary with the HF E-region backscatter boundary in the dusk-midnight sector of the auroral oval. Geophys. Res. Lett. vol. 29, is. 8, pp. 97-1–97-4. DOI: https://doi.org/10.1029/2001GL014184 18. JAYACHANDRAN, P. T., DONOVAN, E. F., MACDOUGALL, J. W., MOORCROFT, D. R., ST-MAURICE, J.-P. and PRIKRYL, P., 2002. Super DARN E-region backscatter boundary in the dusk-midnight sector – tracer of equatorward boundary of the auroral oval. Ann. Geophys. vol. 20, pp. 1899–1904. DOI:  https://doi.org/10.5194/angeo-20-1899-2002